The role of dispositional employability in determining individual differences in career success - Maslić Seršić, Darja (Array, 2014)
The purpose of the study was twofold: (1) to reassess the model of DE proposed by Fugate and Kinicki (2008) in Croatian society, and (2) to validate a new measure of DE through testing its discriminant and incremental validity in relation to CSE. A Croatian version of the scale of DE was constructed based on a qualitative study and applied to a sample of 966 Croatian employees of various demographic and work characteristics. In addition, the CSES (Judge et al., 2003) was applied, as well as four criterion variables: subjective career success, general job satisfaction, relative income and perceived employability. A CFA was performed to test whether the measures of DE and CSE were assessing two distinct dimensions. The results are in line with the hypothesis of the discriminant validity of the constructs. All standardized factor loadings were statistically significant and higher than .70, supporting the scale validity of the measures of DE and CSE, and correlation between the two second-order factors amounted to .50. Results of linear regression analyses showed that DE accounted for additional variance of subjective career success, job satisfaction and perceived employability above and beyond control variables and CSE. Although these findings supported the incremental validity of the model of DE in predicting positive work outcomes, the practical value of the measure should be examined more extensively in future. Limitations of the present study are discussed, and recommendations for future research in the area are given.